Structural-semantic and functional peculiarities of Ukrainian folk charms with dialogs (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article is devoted to the semantic, structural and functional peculiarities of Ukrainian folk charms with dialogs. These peculiarities are provoked by task, magic function of folk charms, by original of world outlook system which magic texts are created and used in.
Keywords: folk charm; text structure; magic word outlook